1999
DOI: 10.1007/s004240050905
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 mediates 70-kDa heat shock protein induction due to ultraviolet irradiation in human skin fibroblasts

Abstract: Ultraviolet B (UVB) alters the expression of heat shock protein 70 (HSP70) in cultured fibroblast cells derived from human skin. However, the nature of the signal transduction pathway remains to be determined. Transforming growth factor-beta (TGF-beta) has a large variety of biological functions, including cell growth control, modulation of inflammation and immunoregulation. In this study, we examined whether TGF-beta is associated with the process of HSP70 expression induced by UVB irradiation. The constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 26 publications
0
39
1
2
Order By: Relevance
“…TGF-β1 is an attractive candidate as an anti-inflammatory and cytoprotective signaling molecule in response to volatile anesthetic treatment as: (1) it has been shown to be released in response to cell surface PS membrane externalization [9,10,11,12,13]; (2) it has potent anti-inflammatory effects and inhibits leukocyte adhesiveness, and (3) exogenous TGF-β1 reduces IR injury in many organ systems [14,15,16]. Moreover, TGF-β1 is a well-known activator of ERK and Akt signaling and TGF-β1 causes upregulation of HSP70 in several cell lines [23,24,25]. We previously demonstrated that sevoflurane caused phosphorylation of ERK and Akt and upregulated HSP70 in human proximal tubule (HK-2) cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is an attractive candidate as an anti-inflammatory and cytoprotective signaling molecule in response to volatile anesthetic treatment as: (1) it has been shown to be released in response to cell surface PS membrane externalization [9,10,11,12,13]; (2) it has potent anti-inflammatory effects and inhibits leukocyte adhesiveness, and (3) exogenous TGF-β1 reduces IR injury in many organ systems [14,15,16]. Moreover, TGF-β1 is a well-known activator of ERK and Akt signaling and TGF-β1 causes upregulation of HSP70 in several cell lines [23,24,25]. We previously demonstrated that sevoflurane caused phosphorylation of ERK and Akt and upregulated HSP70 in human proximal tubule (HK-2) cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins (HSPs) are produced by cells and tissues in response to various stressful conditions, including cold [17], UV light [18], wound healing or tissue remodeling [19]. Recently, accumulated evidences indicated that HSPs are aberrantly overexpressed in many types of human cancers and play critical roles in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Their amount increases rapidly when cells are subjected or exposed to a wide variety of stresses such as heat, xenobiotics or drugs; pathological stimuli such as viral, bacterial and parasitic infections, inflammation and autoimmunity (Wu & Tanguay, 2006). In skin biopsy we can explore the expression of HSPs by WB and qRT-PCR (Cao et al, 1999;Rossner et al, 2003).…”
Section: Heat-shock Proteins (Hsps)mentioning
confidence: 99%